Curatorial voice - Coleman, Laura-Edythe, 1975- author. Link Link
1 online resource (120 pages)
Keywords: Curatorial Voice considers the act of curation from a scientific perspective. Questioning the role of curators, the actual act of curation, and the very sound of curatorial voice, Coleman works to dispel the stereotypes that have historically shrouded the work of curators in mystery.This book draws upon groundbreaking, collaborative research conducted in five national museums in the United States and includes the voices of a diverse range of curators, who reflect, in their own words, upon their role in the construction of curatorial voice. Explaining how the curators used the Curatorial Gatekeeping Mechanisms Chart, created in partnership with the author and included in this book, Coleman demonstrates that the Chart can be used to explain difficult curatorial decisions, to start conversations about shared authority within the museum, and to articulate the value of culture to various museum stakeholders. Most importantly, perhaps, this book and the Chart will provide curators with new tools to explain and justify their valuable work to others and other readers with new ways to understand the role of museums in society.Curatorial Voice will be essential reading for museum professionals around the world, as well as scholars and students with an interest in museums, galleries, and heritage sites. It will be particularly useful to those engaged in the study of curating, collections management, and exhibition design.